MICROWAVE ABSORBERS BASED ON MÖBIUS STRIP RESONATORS - Olga V. BOIPRAV; Vadim A. BOGUSH; Vladislav S. CHELYADINSKY (European Journal of Materials Science and Engineering, 2024)
The paper deals with technology of manufacturing of microwave absorbers with ordered and structured surface layer. This layer contains Möbius strip resonators, located on the fixed distance from each other. The technology was developed by the authors on the base of the following data: 1) results of theoretical study of microwaves interaction with Möbius strip resonator; 2) results of experimental study of electromagnetic radiation reflection, transmission and absorption coefficients in the microwave frequency range of the experimental samples of microwave absorbers based on Möbius strip resonators, which differ by the distance between these resonators. It was established on the base to the listed results that the microwave absorbers manufactured in accordance to the technology proposed by the authors are wideband ones. Electromagnetic radiation absorption coefficient values of these absorbers changes from 0.5 to 0.97 in frequency range 2.0–17.0 GHz if the distance between the Möbius strip resonators containing in their surface layer, is 15.0 mm. If the distance between the Möbius strip resonators containing in the surface layer of the considered absorbers is less than 15.0 mm their electromagnetic radiation absorption coefficient in the indicated frequency bands is lower than presented values. The considered absorbers are promising for use in shielded rooms and anechoic chambers.